Catamnesis of children from mothers who had A(H1N1)pdm09 influenza during pregnancy - D. A. Tarbaeva; T. Y. Belokrinitskaya; T. I. Papkina; A. A. Gerasimova; O. O. Grigoryeva; M. S. Gomboeva; A. A. Dorzhizhapova; Y. B. Bolotova; A. T. Bazarova; A. D. Zhamsaranova (Acta Biomedica Scientifica)
The aim of this study was to assess 5-years catamnesis of children from mothers who had A(H1N1)pdm09 influenza during pregnancy. The design of the research: cohort cross-sectional retrospective "case - control" study. The study group included 227 children of mothers who had A(H1N1)pdm09 influenza during pregnancy, and the control group was consisted of 227 children whose mothers didn't have A(H1N1)pdm09 influenza in epidemic period during pregnancy. It was shown that 11,9 % of children born to mothers with influenza infection during pregnancy vs 1,8 % of children of the control group to 5-year age formed a cohort of patients with recurrent respiratory tract infections (p < 0,001). Acute respiratory infections were complicated by pneumonia in 15,4 % of study group children vs 8,8 % of children in the comparison group (p = 0,044). We founded a significant association between maternity A(H1N1)pdm09 influenza during 1st and 2nd trimesters of gestation and increased frequency of asthma in their children.